2010
DOI: 10.5194/acp-10-3027-2010
|View full text |Cite
|
Sign up to set email alerts
|

Cross-hemispheric transport of central African biomass burning pollutants: implications for downwind ozone production

Abstract: Abstract. Pollutant plumes with enhanced concentrations of trace gases and aerosols were observed over the southern coast of West Africa during August 2006 as part of the AMMA wet season field campaign. Plumes were observed both in the mid and upper troposphere. In this study we examined the origin of these pollutant plumes, and their potential to photochemically produce ozone (O 3 ) downwind over the Atlantic Ocean. Their possible contribution to the Atlantic O 3 maximum is also discussed. Runs using the BOLA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 41 publications
(40 reference statements)
2
66
1
Order By: Relevance
“…An interesting extension of this work would be to implement the same analysis considering the whole monsoon season in order to characterize on the longer term (and larger scale) the impact of central/west African convection on the UT. Climatological analysis of METEOSAT data (Laing et al, 2008) shows Sahelian cold clouds often formed over Nigeria, Chad and Sudan, and possibly fed by trace species from biomass burning sources (Mari et al, 2008;Real et al, 2010). Extensive regional model simulations coupled with satellite data analysis would be necessary to quantify their impact on upper tropospheric composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting extension of this work would be to implement the same analysis considering the whole monsoon season in order to characterize on the longer term (and larger scale) the impact of central/west African convection on the UT. Climatological analysis of METEOSAT data (Laing et al, 2008) shows Sahelian cold clouds often formed over Nigeria, Chad and Sudan, and possibly fed by trace species from biomass burning sources (Mari et al, 2008;Real et al, 2010). Extensive regional model simulations coupled with satellite data analysis would be necessary to quantify their impact on upper tropospheric composition.…”
Section: Discussionmentioning
confidence: 99%
“…West Africa is characterized by the presence of potentially important and poorly known sources of aerosol and ozone precursors. Large latitudinal variability of nitrogen oxides emissions in West Africa during the wet season was observed during AMMA and is reported by Stewart et al (2008); NO x levels in the Sahelian area are high leading to higher ozone mixing ratios (Saunois et al, 2009) while ozone precursors from biomass burning in the southern hemispheric African continent can be transported by deep convection in the upper troposphere up to 10 • N (Mari et al, 2008;Real et al, 2010).…”
mentioning
confidence: 99%
“…There is a positive correlation between CO and the particle mixing ratio because of the import of pollution from upwind tropospheric sources like Asia and India for SCOUT-AMMA and from Indonesia (in connection with strong convective activity there) for Darwin (Brunner et al, 2009). Real et al (2010) showed that biomass burning activities took place in Central Africa at the time of the SCOUT-AMMA campaign and that these significantly influenced the air over West Africa. Air parcels of a given CO abundance contained higher aerosol loadings (upper "branch" in the middle panel of Fig.…”
Section: Vertical Profiles Of Submicron Particle Mixing Ratios In Thementioning
confidence: 99%
“…Fierli et al (2010), used a regional mesoscale model together with the M-55 "Geophysica" observations of water vapour, ozone, CO 2 , and aerosol to demonstrate that signatures of the detrainment from deep convection of mesoscale convective systems can be found as high as 17 km, and possibly higher in some cases. Furthermore, the vertical ozone profiles seem to indicate (Homan et al, 2010) Cross hemispheric transport: Real et al (2010) used BOLAM mesoscale model calculations in conjunction with trace gas measurements to confirm the presence of biomass burning plume remnants from central African fires in the upper troposphere. These were sampled during the M-55 "Geophysica" flight on 13 August 2006 with corresponding signatures in CO, CO 2 , NO, NOy, and submicron aerosols.…”
Section: Atmospheric Background In 2005 and 2006mentioning
confidence: 99%
“…Particulate matter is tiny particles suspended in the air and depending on their size and the meteorological conditions can travel great distances around the globe (Uno et al, 2009;McKendry et al, 2007). Some occur naturally: biogenic substances ), volcanoes (O'Neill et al, 2012Schumann et al, 2011;Winker et al, 2012), dust storms (Ben-Ami et al, 2009;Fischer et al, 2011;Liu et al, 2008;McKendry et al, 2009;Yumimoto et al, 2010), forest and grassland fires (Dirksen et al, 2009;McKendry et al, 2011) and sea spray (Kunz et al, 2002), while others result from human activities (anthropogenic), such as burning fossil fuels (Komppula et al, 2012), industrial by-products (Strawbridge, 2006) and altering natural surface cover (Real et al, 2010). Obtaining vertical profiles of tropospheric aerosols provides critically important information towards understanding climate, air quality and visibility.…”
Section: Introductionmentioning
confidence: 99%